2021
DOI: 10.3390/biom11121761
|View full text |Cite
|
Sign up to set email alerts
|

An Insight of RuBisCO Evolution through a Multilevel Approach

Abstract: RuBisCO is the most abundant enzyme on earth; it regulates the organic carbon cycle in the biosphere. Studying its structural evolution will help to develop new strategies of genetic improvement in order to increase food production and mitigate CO2 emissions. In the present work, we evaluate how the evolution of sequence and structure among isoforms I, II and III of RuBisCO defines their intrinsic flexibility and residue-residue interactions. To do this, we used a multilevel approach based on phylogenetic infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 83 publications
(172 reference statements)
0
7
0
Order By: Relevance
“…This suggested that both the residues proximal to the ligand and those far from the ligand were important for interspecies comparison, which could not be obtained from sequence information alone. Our results thus suggest that substrate-residue interactions can be an essential feature to understand the enzymatic evolution of RuBisCO and may provide a novel insight complementary to that obtained in a recent computational approach [ 28 ]. Methodologically, the present scheme can be used to find closely related enzymes with different substrates, which is quite difficult using classical alignment methods.…”
Section: Discussionmentioning
confidence: 62%
“…This suggested that both the residues proximal to the ligand and those far from the ligand were important for interspecies comparison, which could not be obtained from sequence information alone. Our results thus suggest that substrate-residue interactions can be an essential feature to understand the enzymatic evolution of RuBisCO and may provide a novel insight complementary to that obtained in a recent computational approach [ 28 ]. Methodologically, the present scheme can be used to find closely related enzymes with different substrates, which is quite difficult using classical alignment methods.…”
Section: Discussionmentioning
confidence: 62%
“…Indeed, the photosynthetic gene cluster is located in plasmids of several Rhodobacterales ( 26 ) but not in Acetobacteraceae ( 45 ). The most evident LGT cases of photosynthetic traits in Acetobacteraceae regard the Rubisco present in Elioraea thermophila and two environmental MAGs, which belong to Form IA typical of gamma- and betaproteobacteria ( 27 ). In the case of PufM, there are likely LGT instances from Acetobacteraceae to other taxa, either somehow related, such as Skermanella , or clearly unrelated, such as deltaproteobacteria MAGs (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The presence of at least two Puf subunits of the photosynthetic reaction center is indicated by “Yes,” and the same applies to the presence of the major Crt genes for the biosynthesis of carotenoids following the spirilloxanthin pathway ( 26 ). The presence of CO 2 -fixing Form I Rubisco ( 27 ) is also indicated by “Yes.” b Mean value of the listed taxa of the Roseomonas clade, Roseomonadaceae . …”
Section: Introductionmentioning
confidence: 99%
“…Rubisco large subunit harbouring the catalytic site is encoded by the RbcL gene, which therefore has a major influence on Rubisco kinetic properties ( Kellogg and Juliano, 1997 ; Camel and Zolla, 2021 ). From the literature, 165 C 3 and C 4 plant Rubisco in vitro Kcat values (25 °C pH near 8), 170 in vitro Sc/o values, and 170 in vitro Kc values, as well as corresponding RbcL sequences, were obtained ( Supplementary Table S1 ; Jordan and Ogren, 1983 ; Lehnherr et al , 1985 ; Uemura et al , 1997 ; Kubien et al , 2008 ; Savir et al , 2010 ; Viil et al , 2012 ; Galmés et al , 2014a , b ; Hermida-Carrera et al , 2016 ; Prins et al , 2016 ; Sharwood et al , 2016 ; Long et al , 2018 ; Flamholz et al , 2019 ).…”
Section: Methodsmentioning
confidence: 99%
“…Form IB Rubisco proteins found in plants and green algae consist of both large and small subunits, and the large subunits contain the Rubisco active site. Thus, it has long been assumed that the large subunit sequence variation contributes to the diversity of Rubisco kinetics ( Kellogg and Juliano, 1997 ; Camel and Zolla, 2021 ). Rubisco is often characterised as having a slow turnover rate (Kcat) for CO 2 and poor specificity for CO 2 compared with O 2 (Sc/o; but see Tcherkez et al , 2006 ).…”
Section: Introductionmentioning
confidence: 99%